2016
DOI: 10.1002/jcp.25441
|View full text |Cite
|
Sign up to set email alerts
|

Gene and MicroRNA Expression Are Predictive of Tumor Response in Rectal Adenocarcinoma Patients Treated With Preoperative Chemoradiotherapy

Abstract: Preoperative chemoradiotherapy (pCRT) followed by surgery is the standard treatment for locally advanced rectal cancer (LARC). However, tumor response to pCRT is not uniform, and there are no effective predictive methods. This study investigated whether specific gene and miRNA expression are associated with tumor response to pCRT. Tissue biopsies were obtained from patients before pCRT and resection. Gene and miRNA expression were analyzed using a one-color microarray technique that compares signatures between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 55 publications
2
61
1
Order By: Relevance
“…In the present study, we demonstrated that miR-194 was upregulated in responders patients by analysing its expression profile in a cohort of patients with LARC, in which we performed a miRNA microarray expression profile analysis 14. Recent data have shown that miR-194 plays an important part in tumourigenesis.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the present study, we demonstrated that miR-194 was upregulated in responders patients by analysing its expression profile in a cohort of patients with LARC, in which we performed a miRNA microarray expression profile analysis 14. Recent data have shown that miR-194 plays an important part in tumourigenesis.…”
Section: Discussionmentioning
confidence: 59%
“…The cohort comprises n=38 patients with primary adenocarcinoma of the rectum, who underwent pCRT followed by surgery at our institution (First Surgery Clinic, University of Padova), in which we reanalysed our public microarray miRNA expression profile dataset (GEO dataset: GSE68204) 14. The microarray data platform was Agilent-021827 Human miRNA Microarray (V3).…”
Section: Methodsmentioning
confidence: 99%
“…XRCC3 is over-expressed in rectal cancer patients responding to preoperative chemoradiotherapy (pCRT) followed by surgery compared with those non-responders, the deregulation of which is extensively involved in the chemo-resistance mechanism [11]. Recent articles demonstrate that two gene sets of dysregulated genes could predict pCRT response in patients with rectal adenocarcinoma, one gene set is AKR1C3, CXCL11, CXCL10, IDO1, CXCL9, MMP12, HLA-DRA and another gene set is TMEM188, ITGA2, NRG, TRAM1, BCL2L13, MYO1B, KLF7,and GTSE1 [12, 13]. microRNAs (miRNAs) are small non-coding RNAs, which negatively regulates mRNA expression of targeted genes.…”
Section: Introductionmentioning
confidence: 99%
“…It is encouraging that several putative miRNA biomarkers are reportedly associated with cancer response to preoperative chemoradiotherapy [10]. At present, it is still hard to explain the difference in radiosensitivity difference among patients.…”
Section: Introductionmentioning
confidence: 99%